دراسة تلوث عسل النحل ببعض العناصر الثقيلة في المنطقة الساحلية السورية خلال فصل الخريف لعام .2012 - مكيس, خليل; حمود, فينا; تركماني, نور (Latakia University Journal -Biological Sciences Series, 2016)
أجريت هذه الدراسة في المنطقة الساحلية السورية، وتم جمع عينات عسل النحل من ثمانية مواقع مختلفة تابعة لمحافظتي اللاذقية وطرطوس خلال فصل الخريف لعام 2012، وتقدير محتواها من العناصر الثقيلة (الزنك، والنحاس، والرصاص والكادميوم) بوساطة جهاز الامتصاص الذري في المعهد العالي لبحوث البيئة بجامعة تشرين. أظهرت نتائج التحليل أن تركيز الزنك في عينات عسل النحل تراوح بين 2.86 و12.64 مغ/ك، (متوسط 7.98±3.67)، والنحاس بين 0.125 و0.652 مغ/كغ (متوسط 0.328± 0.176)، والرصاص بين 0.084 و0.378 مغ/كغ (متوسط 0.205± 0.112)، والكادميوم بين 0.0002-0.0132 مغ/كغ (متوسط 0.0053±0.0052). وتبين من النتائج أن أكبر تركيز للعناصر الثقيلة كان في عينة العسل المأخوذة من المنحل الواقع في المدخل الشرقي لمدينة اللاذقية (قرب معمل الجود)، بينما كانت أقل التراكيز للزنك والرصاص في منطقة بانياس (وادي السقي)، وللنحاس في صافيتا، وللكادميوم في منطقة جبلة (قلعة بني قحطان). وبمقارنة تركيز العناصر في عينات العسل المدروسة، وجد أن تركيز الزنك كان الأعلى، يليه النحاس، ثم الرصاص، وأخيراً الكادميوم. وتشير نتائج التحليل الإحصائي إلى وجود فروق معنوية بين المواقع المدروسة خلال فصل الخريف لعام 2012. This study was conducted in the Syrian coastal region, and the honey samples have been collected from eight different sites belonging to the provinces of Latakia and Tartous during the autumn of 2012. Their content of heavy metals (zinc, copper, lead & cadmium) was estimated by Atomic Absorption at the Higher Institute for Environmental Research at Tishreen University. The results showed that zinc concentration in the bee honey samples ranged from 2.86 to 12.64 mg / kg (mean 7.98±3.67), and copper ranged from 0.125 to 0.652 mg / kg (mean 0.328±0.176 ), lead ranged from 0.084 to 0.378 mg / kg (mean 0.205±0.112), cadmium ranged from 0.0002 to 0.0132 mg / kg (mean 0.0053±0.0052). The results indicated that the largest amounts of heavy metals were found in honey sample taken from the apiary which is located at the eastern entrance of Latakia city (near Joud factory), while the lower concentrations of zinc and lead were in Banias area (Wadi Al Saqi), and the least concentration of copper was in Safita area, and of cadmium was in the Gablah area (Bani Qahtan Castle).Comparing elements concentration in the studied honey samples, Zinc concentration was found to be the highest, followed by copper, lead and then finally cadmium.The results of statistical analysis indicated the existence of significant differences between the studied sites during the autumn of 2012.